Catechin-incorporated dental copolymers inhibit growth of Streptococcus mutans (Journal of Applied Oral Science, 2013)
Objective: To test the inhibitory growth activity of green tea catechin incorporated into dental resins compared to resins containing the broad-spectrum antimicrobial compound chlorhexidine against Streptococcus mutans in vitro. Material and Methods: The minimum inhibitory concentrations (MICs) of epigallocatechin-gallate (EGCg) and chlorhexidine (CHX) were determined according to the microdilution method. Resin discs (5 mm × 3 mm) were prepared from Bis-GMA/TEGDMA (R1) and Bis-GMA/CH3Bis-GMA (R2) comonomers (n=9) containing: a) no drug, b) EGCg, c) CHX. Two concentrations of each drug (0.5× MIC and 1× MIC) were incorporated into the resin discs. Samples were individually immersed in a bacterial culture and incubated for 24 h at 37°C under constant agitation. Cell viability was assessed by counting the number of colonies on replica agar plates. Statistical analysis was performed using one-way ANOVA, Tukey and Student t-tests (α=0.05). Results: Both resins containing EGCg and CHX showed a significant inhibition of bacterial growth at both concentrations tested (p